Energy: prospects and challenges in the 1980's - Wong, K. K. (1982)
The prospects for Malaysia m the-energy field are great. We have the fossil fuels to push us through a more self-reliant and independent economy if we apply a process of multifactorial bargaining in our energy policy and orograrnmes. The future for photovoltaic is great and can be great for Malaysia in particular and the ASEAN countries in general. While realising that such a possibility exists we must also take up the conservation challenge for we are now moving in the transition from an agrarian based economy to a more industrialised economy. Conservation can only take place if we have the facts and data at our finger tips to monitor energy end uses and to implement public policies to manage our limited energy reserves. The conservation issue was a $350 million question in 1980 and is therefore a very important question. Subsidies for both diesel and kerosene should be re-evaluated in the light of energy inefficiencies created by such a government programme. Subsidies cost the government $860 million in 1980. A gradual reduction with proper measures to assist the lower income users must be sought. In the post Stockholm era we must strive for not only economic development but also human development. Both these developments must be sustained in the long run. and both these require a reasonable amount of energy. In the development of human skills in energy technology we must avoid tum-key type projects and go for well negotiated projects which include training at all levels such that there is TOTAL technology transfer. Technology cannot stand on its own. It must be supported by fundamental pursuits of science in the energy field. This can only take place if we pool out efforts together as an ASEA.N entity. Scientific research is the way to go, to back us on the industrial front. We must wake up to this reality in the 80's and must accordingly inject money into it. The prospects for energy are good but the challenges are even greater. We must stand up to the challenges and weather the storms along the way.